2018
DOI: 10.1534/g3.117.300199
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction and Association Mapping of Curd-Related Traits in Gene Bank Accessions of Cauliflower

Abstract: Genetic resources are an important source of genetic variation for plant breeding. Genome-wide association studies (GWAS) and genomic prediction greatly facilitate the analysis and utilization of useful genetic diversity for improving complex phenotypic traits in crop plants. We explored the potential of GWAS and genomic prediction for improving curd-related traits in cauliflower (Brassica oleracea var. botrytis) by combining 174 randomly selected cauliflower gene bank accessions from two different gene banks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 87 publications
2
30
0
Order By: Relevance
“…Contrary, Singh et al (2017) reported that soil application of Borax (20 kg/ha) combined with Sodium molybdate (2 kg/ha) as sources of B and Mo, respectively, accelerated the early mature yield of cauliflower. However, insignificant effects of nitrogen, micronutrient application and their interaction on number of days to maturity might be due to its high heritability, whereas, it was reported that number of days to budding is a highly heritable trait (86 and 94%), which indicates that this trait is stable and not strongly affected by environmental factors (Yousef et al, 2015;Thorwarth et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary, Singh et al (2017) reported that soil application of Borax (20 kg/ha) combined with Sodium molybdate (2 kg/ha) as sources of B and Mo, respectively, accelerated the early mature yield of cauliflower. However, insignificant effects of nitrogen, micronutrient application and their interaction on number of days to maturity might be due to its high heritability, whereas, it was reported that number of days to budding is a highly heritable trait (86 and 94%), which indicates that this trait is stable and not strongly affected by environmental factors (Yousef et al, 2015;Thorwarth et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the specific curd phenotype is revealed to be governed by BoCAL gene [2,3], BoAP1 gene determines the divergence between cauliflower curd and broccoli head phenotypes [4,5], while the Or Gene encoding a plastid associated protein results in an orange curd that is rich in β-carotene [6]. Recently, a genome wide association study based on 174 randomly selected cauliflower gene bank accessions identified a total of 24 significant associations for curd-related traits [7].…”
Section: Introductionmentioning
confidence: 99%
“…() showcased the method's power for mapping natural genetic variants for more than 100 traits in A. thaliana . To date, GWAS have also identified the genetic basis of numerous agronomic traits, speeding up breeding programs of crops such as maize (Jiao et al ., ; Zila et al ., ; Wallace et al ., ; Hu et al ., ; Xu et al ., ) and rice (Huang et al ., , ; McCouch et al ., ; Wang et al ., ; Wang et al ., ), as well as crops with less well‐developed molecular resources such as wheat (Liu et al ., ; Kristensen et al ., ), soybean (Fang et al ., ), barley (Sharma et al ., ), cotton (Fang et al ., ; Du et al ., ), cassava (Kayondo et al ., ), foxtail millet (Jia et al ., ), spinach (Ma et al ., ) and cauliflower (Thorwarth et al ., ). GWAS are a particularly relevant tool for perennial species such as apple (Urrestarazu et al ., ), citrus (Minamikawa et al ., ), eucalyptus (Resende et al ., ) and poplar (Liu et al ., ).…”
Section: Finding Associations Between Genotype and Phenotype: Linkagementioning
confidence: 97%